Soya - a rich source of protein, oil and income - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
Linley Banda grows soya beans on her farm in southern Malawi. She likes the crop because it needs less inputs than maize. She sells most of her soya beans to food processors.